Experimental Evidence of a Link Between Lightning and Magnetic Field Fluctuations in the Upper Ionosphere Observed by Swarm. Issue 4 (12th February 2021) - Strumik, M.; Slominski, J.; Slominska, E.; Mlynarczyk, J.; Blecki, J.; Haagmans, R.; Kulak, A.; Popek, M.; Martynski, K.; Wronowski, R.
Abstract: We present results of analysis of lightning observations and satellite measurements of ionospheric magnetic field fluctuations in the ultralow frequency (ULF) range. The fluctuations are measured by Swarm satellites, while the lightning observations are provided by the Geostationary Lightning Mapper (GLM) and the World ELF Radiolocation Array (WERA). We identify spatio‐temporal relationships that demonstrate a leakage of electromagnetic fluctuations caused by lightning into the upper ionosphere. Causal association between the two phenomena is evidenced by investigating relations between lightning and fluctuation properties. The presented results suggest that lightning generate ULF fluctuations in the ionosphere that can be detected by satellites, if the lightning‐satellite geographic distance is less than ∼5°. Typical properties of the fluctuations caused by lightning are described in the paper. To our knowledge, this is the first direct experimental confirmation of a link between lightning and magnetic field fluctuations in the upper ionosphere in the ULF range. Plain Language Summary: It has been a matter of interest, if electromagnetic fluctuations caused by lightning can propagate from the lower atmosphere higher into the ionosphere, which is an ionized and electrically conducting medium. This process requires conversion of the electromagnetic perturbation propagating in the neutral atmosphere into an ionospheric plasma wave, which for ultralow frequencies (ULF) can attenuate strongly the wave amplitude. The attenuation is considered to be rather significant, thus one could argue that it is virtually not possible to observe the ionospheric magnetic field perturbations caused by lightning using currently available satellite magnetometers. There are many remote observations of lightning and direct satellite measurements of ionospheric magnetic field fluctuations, that can be analyzed searching for a possible link between the two phenomena. Using Swarm satellite measurements and two types of lightning observations, we provide an evidence that lightning generate electromagnetic perturbations that propagate into the upper ionosphere and can be measured with magnetometers onboard low‐Earth orbit satellites, for example, by the Swarm constellation. We reveal links between lightning and ionospheric wave properties, that suggest a real causality relationship between the two phenomena. To our knowledge, this is the first direct experimental confirmation of such a relation in the ULF range. Key Points: Lightning can generate ultralow frequency (ULF) fluctuations leaking into the upper ionosphere Observations show that the fluctuation amplitude is proportional to the lightning charge moment The ULF fluctuations generated by lightning can be detected by low‐Earth orbit satellites, for example, the Swarm constellation